The great women : mengapa wanita harus merasa tidak lebih mulia / Muhammad Ali Al-Allawi ; penerjemah El-Hadi Muhammad ; penyunting Dendi Irfan, Arif Anggoro, Ahmad Budiyanto. - AL-ALLAWI, Muhammad Ali; Ahmad Budiyanto; Arif Anggoro; Dendi Irfan; El-Hadi Muhammad (Pena Pundi Aksara, 2016)
xii, 369 hlm. ; 20 cm